DISPLAYED OBJECTS OF THE PAVILION OF INDONESIA AT THE 1986-1992 WORLD EXPO AS REPRESENTATION OF THE NEW ORDER’S IDEOLOGY - Tjahjawulan, Indah (UI Scholars Hub, 2020)
This research delves into the pavilions of Indonesia in World Expo, which is a world class cultural event involving so many countries all over the world as participants and it also attracts millions of people coming to the event of 3 to 6 months duration. Throughout the administration of Soeharto under the regime of New Order Indonesia had participated in six World Expo events out of ten events being organized; this shows how important the role of this event for Indonesia. However, from one Expo to another, it is curious that the objects chosen to be displayed in the pavilion are in fact a repetition so it raises question whether there is a certain concept being emphasized in each Expo event that the New Order regime would like to pass on by means of the displayed items continuously and whether such repetition can be considered as a form of framing and a confirmation of the symbol of power that the New Order want to show. This research is a cultural studies using qualitative approach that delve in data taken from a variety of documents such as photographs, reports compiled by committees, newspaper, magazines and internet. Data is scrutinized with semiotics analysis and theories of semiotics and framing in order to see how text is regarded as message by way of reading the created representation closely and also how the context of New Order government tried to ‘package’ it and to put the focus on the elements of objects of display in Indonesia’s pavilion at the World Expo. This research results in findings that uncover (1) meaning and representation of the objects of display of the 1986, 1988, 1992 and (2) representation of objects of display in the pavilion of 1986, 1988 and 1992 World Expo as construction of the ideology of New Order